2008
DOI: 10.1108/01445150810904468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of temperature and properties at interface of AISI 1040 steels joined by friction welding

Abstract: Purpose -The purpose of this paper is to evaluate temperature and properties at interface of AISI 1040 steels joined by friction welding. Design/methodology/approach -In this study, AISI 1040 medium carbon steel was used in the experiments. Firstly, optimum parameters of the friction welding were obtained by using a statistical analysis. Later, the microstructures of the heat-affected zone are presented along with micro hardness profiles for the joints. Then, the temperature distributions are experimentally ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…6, between 0.75 and 0.95 of T m (solidus)). 32 33 34 35 36 3738 Experiments show that the material type has little effect on the normalised interface temperature with the exception of Ti alloys. It is possible that a lower thermal diffusivity together with a pronounced decrease in strength at elevated temperatures are affecting the relatively low interface temperatures recorded for Ti alloys.
6 Normalised interface temperature during FW (T m refers to solidus)
…”
Section: Process Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…6, between 0.75 and 0.95 of T m (solidus)). 32 33 34 35 36 3738 Experiments show that the material type has little effect on the normalised interface temperature with the exception of Ti alloys. It is possible that a lower thermal diffusivity together with a pronounced decrease in strength at elevated temperatures are affecting the relatively low interface temperatures recorded for Ti alloys.
6 Normalised interface temperature during FW (T m refers to solidus)
…”
Section: Process Parametersmentioning
confidence: 99%
“…9 b ) as experiments showed. 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44,45 Another process parameter, the welding pressure at high enough values affects material expulsion rate from the interface. Bhamji et al 21 found that it is proportional to burn-off rate, and inversely proportional to the required friction time once a limit has been passed.
9 Relationship between average heat input and axial shortening for Ti64 a 43 and mild steel b 44 obtained by numerical modelling
…”
Section: Process Parametersmentioning
confidence: 99%